Impact of fires and regional biomass burning on Bogotá's air quality : statistical analysis and a Lagrangian transport analysis (2019)
Biomass burning emissions have a substantial impact on regional air quality and climate. The region of Amazonia in South America has long been identified as one of the largest contributors to short-lived pollutants globally. However, massive natural wildfires and agricultural burns also occur every year in the grassland plains of Northern South America during the dry season (November to April). The regional-scale air quality impact of these biomass burning emissions has not been studied in depth and is analyzed in this study. This research has been established in two chapters. In chapter 1 of this document, we used PM2.5 and PM10 concentrations from three large urban areas: Bogotá, Medellín, and Bucaramanga, for the period 2006-2016. CO data was only available for the city of Bogotá for the analysis period. The spatiotemporal distribution of fires was obtained from MODIS Active Fire Data. The back-trajectories of air masses reaching the receptor sites were computed with two different meteorological datasets. Radiosonde data, available only for Bogotá, was used to account for local meteorological factors impacting pollution dispersion. A novel analysis algorithm was developed to combine active fire data with back-trajectory locations to select those active fires in the vicinity of the air masses arriving at each city. This analysis allows the selection of only those fires that can be causally related to the air quality in the selected locations. We show that anomalously high PM and CO levels occurred when air masses originated from the Orinoco grasslands during the times when the largest number of fires in the region were active. Also, statistical techniques were executed to analyses the association between the related number of fires and these pollutants. In chapter 2, novel statistical classification methods are explored to separate the effect of local vs. regional variables affecting the concentration of air pollutants in the city.